Genetic susceptibility to PM2.5 exposure and transcriptional responses in pediatric asthma: insights from single-cell transcriptomics - Kelchtermans, Jelte; Qu, Huiqi; Hou, Cuiping; Mentch, Frank; McGrath-Morrow, Sharon A.; Hakonarson, Hakon (Frontiers in Immunology, 2026)
BackgroundExposure to fine particulate matter (PM2.5) increases asthma severity and reduces glucocorticoid responsiveness in children, yet the molecular mechanisms underlying PM2.5 sensitivity remain unclear. We previously identified a PM2.5-sensitive asthma phenotype and developed a PM2.5 sensitivity polygenic risk score (sPRS) correlated with asthma exacerbations and lung function decline.Research questionWe sought to determine whether genetic variants contributing to PM2.5 sensitivity converge on specific biological pathways or transcriptional regulators, and whether children with a high sPRS exhibit immune transcriptional signatures consistent with heightened PM2.5 susceptibility.MethodsGenes implicated by sPRS variants were mapped using regulatory annotation tools and evaluated for pathway and transcription factor target enrichment. Peripheral blood mononuclear cells (PBMCs) from high- and low-sPRS children matched on long-term ambient PM2.5 exposure were profiled using single-cell RNA sequencing. Donor-level pseudobulk differential expression was performed using a paired quasi-likelihood negative binomial framework, followed by exploratory pathway enrichment and perturbagen signature analyses.ResultssPRS-implicated genes were enriched for transcriptional regulators linked to SMAD2/3- and MAPK-associated signaling, suggesting TGF-β1-related pathway involvement. No genes reached false-discovery-rate-adjusted significance at the donor level in this small, matched cohort. However, secondary pathway-level analyses demonstrated concordant enrichment across multiple immune populations in inflammatory and stress-response signaling programs previously linked to PM2.5 exposure. Perturbagen signature analyses likewise highlighted small-molecule regulators of TGF-β1-associated pathways.InterpretationThese integrative genomic and transcriptomic analyses nominate TGF-β1-SMAD/MAPK signaling as a biologically plausible axis of genetic susceptibility to PM2.5 in pediatric asthma. Given the modest sample size and indirect nature of enrichment-based inference, these findings should be considered hypothesis-generating and motivate targeted functional validation.